Evaluating Supplementary Feeding Program Implementation in a Community-Based Health Service - Santi Effendi; Musmuliadi Musmuliadi; Sabran Sabran (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study evaluates the implementation of a Supplementary Feeding Program (PMT) in in Panji Subdistrict, Tenggarong District, Kutai Kartanegara Regency as a community-based health service , with particular attention to the role of parents in supporting program effectiveness. The study is motivated by the importance of sustained nutrition interventions in improving the nutritional status of children under five, preventing stunting, and strengthening public health outcomes. A qualitative approach with a descriptive evaluative design was employed. Data were collected through in-depth interviews, observations, and document review involving parents, community health volunteers, nutrition officers, and local government representatives. The findings show that parental involvement is reflected in three main dimensions: ensuring children attend community health service activities, understanding the supplementary feeding menu, and applying healthy eating practices at home. In general, parents demonstrated strong commitment to the program, although differences in nutritional literacy remain a major challenge. Parental contributions include emotional support, practical assistance, information sharing, and the adoption of healthy practices in everyday life. Program implementation is also shaped by both enabling and constraining factors. Supporting factors include active community health volunteers, assistance from nutrition personnel, and high parental enthusiasm, whereas inhibiting factors include limited funding, low nutritional literacy, and the absence of working parents during scheduled activities. Overall, the supplementary feeding program has been implemented fairly well, but its long-term effectiveness depends heavily on parental participation and stakeholder collaboration.